2005
DOI: 10.1242/jeb.01732
|View full text |Cite
|
Sign up to set email alerts
|

Optical studies of nicotinic acetylcholine receptor subtypes in the guinea-pig enteric nervous system

Abstract: ErratumObaid, A. L., Nelson, M. E., Lindstrom, J. and Salzberg, B. M. (2005). Optical studies of nicotinic acetylcholine receptor subtypes in the guinea-pig enteric nervous system. J. Exp. Biol. 208, 2981-3001. In the original published on-line version of this paper, the acceptance date was incorrect. It should have read 2 June 2005. The error has been rectified and the current on-line version and print versions are correct.We apologise to authors and readers for any inconvenience this may have caused. 2981… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 77 publications
(90 reference statements)
5
36
0
Order By: Relevance
“…Electrophysiological evidence tallies well with expression studies, showing that 70% of AH neurons show typical α3β4-like responses, whereas the remaining AH neurons and S neurons have a different, and at present uncharacterized, nicotinic response (Galligan & North, 2004). Further electrophysiological studies with subtype-selective peptidic antagonists showed the presence of α3β2 and α3β2β4 responses (Obaid et al, 2005). Low levels of α7 mRNA are expressed in rat myenteric plexus (Garza et al, 2009) and both plexa of guinea pig (Obaid et al, 2005), although functional evidence for α7-like responses in enteric circuits is questioned (Galligan & North, 2004;Obaid et al, 2005).…”
Section: The Enteric Nervous Systemsupporting
confidence: 71%
See 1 more Smart Citation
“…Electrophysiological evidence tallies well with expression studies, showing that 70% of AH neurons show typical α3β4-like responses, whereas the remaining AH neurons and S neurons have a different, and at present uncharacterized, nicotinic response (Galligan & North, 2004). Further electrophysiological studies with subtype-selective peptidic antagonists showed the presence of α3β2 and α3β2β4 responses (Obaid et al, 2005). Low levels of α7 mRNA are expressed in rat myenteric plexus (Garza et al, 2009) and both plexa of guinea pig (Obaid et al, 2005), although functional evidence for α7-like responses in enteric circuits is questioned (Galligan & North, 2004;Obaid et al, 2005).…”
Section: The Enteric Nervous Systemsupporting
confidence: 71%
“…mRNA expression studies in postnatal rats, which are thought to reflect adult expression patterns, showed an autonomic ganglia-like expression pattern of subunits with relatively high levels of α3, α5, and β4 mRNA and lower levels of β2 mRNA in the myenteric plexus of stomach and intestine and relatively low levels of α3, α5, and β4 mRNA in the submucosal plexus of the intestine (Garza, Huang, Son, & Winzer-Serhan, 2009). A similar pattern was observed in immunohistological experiments with subunit-selective monoclonal antibodies (Obaid, Nelson, Lindstrom, & Salzberg, 2005). Accordingly a large predominance of β4* over β2* nicotinic binding was observed in receptor autoradiography studies (Garza et al, 2009).…”
Section: The Enteric Nervous Systemsupporting
confidence: 65%
“…By contrast, evidence for a role of the 3 and 4 subunits in synaptic transmission is strong (for review see [40]). Other evidence indicates that 2 subunits are expressed in enteric neurons [94] and the exact stoichiometry of enteric nAChR remains to be definitively identified.…”
Section: Fast Epsps and The Receptors That Mediate Themmentioning
confidence: 99%
“…In that study, the authors found that nicotinic acetylcholine receptors (nAChRs) that reversibly desensitize following nicotine exposure may be responsible for the enhancement of neuronal activity observed following nicotine application (Obaid et al 1999). The same group then used VSD imaging to show that nAChRs may be capable of regulating the activity of both excitatory and inhibitory pathways (Obaid et al 2005). Similarly, another group used VSD imaging to examine the activity of neurons in the guinea-pig and mouse ENS (Neunlist et al 1999), and have gone on to use this technique to record the activity of cultured human myenteric neurons, recording spike discharge following nicotine application (Vignali et al 2010).…”
Section: Vertebrate Enteric Gangliamentioning
confidence: 99%